Implementation of PT Pertamina Patra Niaga Fuel Terminal Rewulu Corporate Social Responsibility Program through the Traditional Tempe Processing Program (PETRA) by KWM Berlian Progo - Zukhruf Arifin; Rifaldi Maulyansyah; Hasna Fillari Sofia; Kharisma Nisa Pertiwi; Lestari Arum Putri (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
The community empowerment program for the Berlian Progo Independent Women's Group (KWM) is an initiative of PT Pertamina Patra Niaga Fuel Terminal Rewulu's Corporate Social Responsibility (CSR) in 2019. The presence of the Traditional Tempe Processing (PETRA) program is aimed at increasing the productivity of the people of Babakan Hamlet, Poncosari Village , Srandakan District, Bantul Regency, which previously experienced a vacuum due to the freezing of the Covid-19 outbreak. However, the presence of CSR PT Pertamina Patra Niaga Fuel Terminal Rewulu has succeeded in providing enthusiasm and support for the community to rebuild the PETRA program. In this community empowerment program, optimizing the potential of Koro soybeans which are processed into Koro tempeh (raw), Koro tempeh chips, and bacem koro tempeh through the innovation of Biomass automatic hybrid stove burners, namely by traditional innovative methods by means of a hybrid fueled by LPG and environmentally friendly Biomass pellets. This research was conducted to determine the community empowerment implementation program up to the community empowerment stage. The method used by researchers is descriptive qualitative. The presence of KWM Berlian Progo can increase the productivity and economy of Babakan Hamlet...